Recruitment of histone modifications to assist mRNA dosage maintenance after degeneration of cytosine DNA methylation during animal evolution - Chang, Andrew Ying-Fei; Liao, Ben-Yang

(untitled) (Genome Research, 2017)
Following gene duplication, mRNA expression of the duplicated gene is reduced to maintain mRNA dosage. In mammals, this process is achieved with increased cytosine DNA methylation of the promoters of duplicated genes to suppress transcriptional initiation. However, not all animal species possess a full apparatus for cytosine DNA methylation. For such species, such as the roundworm (Caenorhabditis elegans, “worm” hereafter) or fruit fly (Drosophila melanogaster, “fly” hereafter), it is unclear how reduced expression of duplicated genes has been achieved evolutionarily. Here, we hypothesize that in the absence of a classical cytosine DNA methylation pathway, histone modifications play an increasing role in maintaining mRNA dosage following gene duplication. We initially verified that reduced gene expression of duplicated genes had occurred in the worm, fly, and mouse (Mus musculus). Next, several histone marks, with the capacity to control mRNA abundance in the models studied, were examined. In the worm and fly, but not in the mouse, multiple histone modifications were found to assist mRNA dosage maintenance following gene duplication events and the possible involvement of adenine DNA methylation in this process was excluded. Furthermore, the histone marks and acting regions that mediated the reduction in duplicated gene expression were found to be largely organism specific. Thus, it appears that many of the histone marks that maintain mRNA dosage were independently recruited during the evolution of worms and flies to compensate for the loss of cytosine DNA methylation machinery from their genomes.